Pengaruh Pemberian Diet Restriksi Vitamin B12 Pada Tikus: Kajian Insulin dan Glukosa Plasma - Imelda Rosalyn; Dewi Irawati SS; Irena Ujianti; Patwa Amani (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2021)
Background: Deficiency of vitamin B12 remains a health problem in both developed and developing countries. Many journal studies showed an association between deficiency of vitamin B12 and metabolic disorder, one of which is insulin resistance, one of the most significant metabolic diseases. Resistance to insulin may be assessed by changes in plasma glucose and insulin levels. This study explored a possible relationship between vitamin B12 restriction and glucose metabolism. Materials and Methods: This study used an experimental method of 18 male Sprague Dawley rats (Rattus norvegicus, 300-400 gram, age 7-8 months), divided into three groups: control (G1), four weeks treatment group (G2 ) and 12-week treatment group (G3). In the control group, regular feed, the standard diet was given, while the treatment group was assigned vitamin B12, AIN-93M deficiency feed according to the treatment age. Results: Plasma glucose increased in treatment group after 4 weeks (control vs P1= 104.7 ± 5.04 vs 206.8 ± 4.5 p = 0.000) and 12 weeks (control vs P3 = 99.9±6.3 vs 144.7±6.8 p<0.01). Plasma insulin decreased in treatment group after 4 weeks (control vs P1=63.8 ± 1.5 vs 59.9 ± 0.7 p > 0.05) and 12 weeks (control vs P3 = 61.5±0.64 vs 57.4±1 p>0.05). Conclusion: Increased homocysteine deficiency due to dietary vitamin B12 can cause insulin resistance syndrome. As a result, glucose and plasma insulin levels are disrupted Keywords: Homocysteine, vitamin B12 Deficiency, Glucose, Insulin, Insulin Resistance